The Consequences of Radical Reform: The French Revolution - Acemoglu, Daron; Cantoni, Davide; Johnson, Simon; Robinson, James A (American Economic Review, 2011)
The French Revolution had a momentous impact on neighboring countries. It removed the legal and economic barriers protecting oligarchies, established the principle of equality before the law, and prepared economies for the new industrial opportunities of the second half of the 19th century. We present within-Germany evidence on the long-run implications of these institutional reforms. Occupied areas appear to have experienced more rapid urbanization growth, especially after 1850. A two-stage least squares strategy provides evidence consistent with the hypothesis that the reforms instigated by the French had a positive impact on growth. JEL: N13, N43, O47